Effect of Fermentation Time on Molecular Structure and Physicochemical Properties of Corn Ballast Starch - Wei, Chunhong; Ge, Yunfei; Zhao, Shuting; Liu, Dezhi; Jiliu, Junlan; Wu, Yunjiao; Hu, Xin; Wei, Mingzhi; Wang, Yifei; Wang, Weihao; Wang, Lidong; Cao, LongKui (Frontiers in Nutrition, 2022)
The effect of fermentation treatment on the surface morphology, crystal structure, molecular weight, chain length distribution, and physicochemical properties of corn starch was investigated using natural fermentation of corn ballast. The amylose content in corn ballast starch reduced at first after natural fermentation, then grew, following the same trend as solubility. There were certain erosion marks on the surfaces of fermented corn ballast starch granules. The crystalline structure of corn ballast starch remained the same, i.e., a typical A-type crystalline structure, at different fermentation times; however, the intensities of diffraction peaks were different. The weight-average molecular weight of starch first increased and then decreased after fermentation. The content of low-molecular-weight starch (peak 3) decreased from 25.59 to 24.7% and then increased to 25.76%, while the content of high-molecular-weight starch (peak 1) increased from 51.45 to 53.26%, and then decreased to 52.52%. The fermentation time showed a negative correlation with the viscosity of starch, and the pasting temperature first increased, and then decreased. Natural fermentation can be used as a technical means to produce corn starch products as a result of the experiments' findings, and future experiments will detect and analyze the bacterial structure of corn fermentation broth in order to better understand the molecular mechanism of natural fermentation affecting the structure and physicochemical properties of corn starch.